Recovery of Sesamin, Sesamolin, and Minor Lignans From Sesame Oil Using Solid Support-Free Liquid–Liquid Extraction and Chromatography Techniques and Evaluation of Their Enzymatic Inhibition Properties - Michailidis, Dimitris; Angelis, Apostolis; Aligiannis, Nektarios; Mitakou, Sofia; Skaltsounis, Léandros (Frontiers in Pharmacology, 2019)
In this study an integrated process for the recovery of sesamin and sesamolin, two high added-value lignans of sesame oil (SO) was developed, using synchronous extraction and chromatography techniques. The extraction of SO phenolic content was studied using two different extraction techniques: Annular centrifugal extraction (ACE) and centrifugal partition extraction (CPE). The derived data of each experiment were compared in terms of revealing the yields, time and solvents consumption showing that CPE is the most effective technique, concerning the solvent consumption. The isolation of lignans was achieved using centrifugal partition chromatography (CPC) both on semi-preparative and preparative scale. The biphasic system used for this purpose was consisted of the solvents: n-Hex/EtOAc/EtOH/H2O in proportion 2:3:3:2 (v/v/v/v) and direct recovery of the two major lignans sesamin and sesamolin was achieved. In parallel the CPC analysis resulted in the isolation of four minor lignans of sesame oil i.e. samin, sesamol, sesaminol and episesaminol. Structure elucidation of isolated lignans was based on HRMS/MS and NMR experiments. High performance liquid chromatography (HPLC) was employed for quantitative analysis of the obtained extracts to determine the purity of the isolated compounds as well. The results of this study demonstrated that sesamin and sesamolin were recovered in purity higher than 95%, verifying the effectiveness of the purposed separation methodology. Finally, due to the general application of sesame oil in cosmetic industry, all the pure compounds were evaluated for their tyrosinase, elastase, collagenase and hyaluronidase inhibition activity.